2002
DOI: 10.1006/eujc.2001.0562
|View full text |Cite
|
Sign up to set email alerts
|

La 5-reconstructibilité et L’indécomposabilité Des Relations Binaires

Abstract: A binary relation is (≤k)-reconstructible, if it is determined up to isomorphism by its restriction to subsets of at most k elements. In [8], Lopez has shown that finite binary relations are (≤6)-reconstructible. To prove that the value 6 of its result, is optimal, Lopez [3], associates to all finite binary relation, an infinity of finite extensions, that are not (≤5)-reconstructible. These extensions are obtained from the relations given, by creation of intervals. Rosenberg has then asked if all finite binary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
8
0
3
Order By: Relevance
“…. , t 2n ) all of whose neutral edges are full, let R be a relation obtained from S by almost-dilating t 1 …”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation
“…. , t 2n ) all of whose neutral edges are full, let R be a relation obtained from S by almost-dilating t 1 …”
Section: Examplementioning
confidence: 99%
“…The class MD k includes in particular the class of the indecomposable ( k)-deformable relations. The determination of the class MD 5 is obtained in [1] and we characterize here classes MD k for k = 2. The determination of MD 4 follows basically from the properties of the ( 4)-hypomorphy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Lopez [9] a établi la ( 6)-reconstruction des tournois, de plus il a montré que la valeur 6 est optimale. Ensuite, le problème de la ( k)-reconstructibilité pour k ∈ {3, 4, 5} a été étudié dans [1,3]. En particulier, pour k = 3, Y. Boudabbous et G. Lopez [3] ont obtenu le résultat suivant :…”
Section: Introductionunclassified
“…Lopez [9] established that the tournaments are ( 6)-reconstructible and showed that the value 6 is the best possible. The ( k)-reconstructibility problem for k ∈ {3, 4, 5} was studied in [1,3]. In particular, for k = 3, Y. Boudabbous and G. Lopez [3] showed that a tournament is ( 3)-reconstructible if and only if all its intervals are self-dual.…”
mentioning
confidence: 99%
“…G. Lopez a prouvé [6] que tout graphe ayant au moins 7 sommets est 6-reconstructible. La classification des graphes k-reconstructible pour k ∈ {4, 5} a été obtenu par Y. Boudabbous [1] et pour k = 3 par Y. Boudabbous et G. Lopez [2].…”
Section: Introductionunclassified